Management of endocervical polipes in posmenopause - Ayala-Peralta, Félix Dasio (2019)
Endocervical polyps are the most common benign pathologies of the cervix, whose etiology is still unknown. They appear in 2 to 5% of women. In general they originate in the endocervical canal and less frequently from the ectocervix. The case of a 51-year-old woman whose last menstruation date was 2 years ago is presented and goes to a climacteric office for routine, asymptomatic control and a 1x0,5 cm color polypoid tumor is visualized in the gynecological examination. Pink with shortened sessile pedicle, to whom polypectomy is performed and whose histological study reveals endocervical polyp without signs of malignancy.